Management of Heart Failure in the Hospital: A Clinical Approach - Laksono, Sidhi; Syukran (Universitas Ahmad Dahlan, 2023)
Despite tremendous breakthroughs in drug-based and device-based therapy, heart failure continues to be a serious and growing public health issue linked with substantial disability, frequent hospitalization, and large economic expenditures. Complex therapeutic options in a population with a high frequency of comorbidity and overall frailty hinder clinical care. In recent years, significant progress has been made in the care of heart failure (HF). In this study, the most recent available evidence, the indications provided by worldwide guidelines, and expert opinion on the optimal treatment for individuals with HF will be discussed. This review, according to the authors, bridges the gap between guidelines and clinical practice and presents recommendations to improve HF management.